Soil radioactivity in urban parks of Piraeus - Kapsokoli, Eleni; Gelatsoras, Foivos Panagiotis; Siltzovalis, Georgios; Madesis, Ioannis; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2026)
Assessment of natural and artificial radioactivity in soil is essential for understanding environmental radiation exposure and potential health risks. In the present study, the levels of natural and artificial radioactivity in twenty (20) urban parks in Piraeus and the surrounding areas have been assessed extending a study conducted by Gelatsoras et al. in urban parks in the wider Attica region. The focus has shifted on the industrial area around the largest Greek port, which is also a major touristic and transportation hub. High-resolution 𝛾-ray spectroscopy was carried out in properly prepared samples at the recently upgraded Advanced Laboratory for Environmental Radiation Technology (ALERT) at National and Kapodistrian University of Athens. The measured specific activities of NORM (40K, U- and Th-series), as well as of 137Cs, the major Chernobyl fallout tracer, are reported. Overall, the results show a trend in agreement with the average background levels in Greece, with a few exceptions suggesting that further work is required.